(untitled) (Contemporary Central & East European Law, 2024)
Remonstration has long been present in Polish legislation and the practice of law application. It also has a long tradition in other countries, especially the legal systems of the German-speaking area. The genesis of this institution indicates that it was an imperfect (legal) measure, since its consideration depended solely on the goodwill of the ruler or the authority authorized by him. Remonstrance generally “goes hand in hand” with the institution of self-verification, being part of the various forms of self-verification, in many legal systems. Undoubtedly, it is part of the system of self-control, since it allows for the verification of a previously made decision by the same administrative body that made it. Simplification of administrative procedures is a very attractive slogan. For many years, the legal systems of various countries have been looking for legal solutions and systemic solutions to reduce bureaucracy in administration. Simplification of procedures in administration is aimed at reducing excessive and unnecessary formalities in the area of public administration functioning. Achieving this goal is possible in various ways. One of them is the introduction of appropriate legal measures into the system of administrative procedures. An example of these is the institution of “administrative silence”/“tacit settlement of a case by an administrative body”. Remonstration is another example of a legal measure through which a final resolution of a case can be obtained quickly and without unnecessary costs. The legal remedy of remonstration is perfectly in line with the current administrative policy of many countries, striving – on the basis of individual normative solutions – to ensure that each case is resolved quickly, efficiently, effectively and with the least possible involvement of public funds. And it is indisputable that the fastest way to eliminate defects in administrative decisions is to correct them by the same body that issued the decision. Mobilizing the resources at the disposal of a higher level authority, or an administrative court, requires the involvement of greater forces and resources. In contrast, the activation of the internal verification procedure, as a rule, makes it possible to speed up the settlement of the case and avoid many of the inconveniences, including costs, resulting from continuing the appeal procedure. An important advantage of self-monitoring is that it leads to faster handling of the case, and therefore serves to implement the principle of speed of proceedings, as well as promotes the efficiency of proceedings before public administration bodies. Undoubtedly, the use of remonstration also promotes the efficiency of administrative proceedings, since the inclusion of remonstration makes it possible to quickly and efficiently remove the indicated deficiency. This, in turn, reduces the cost of the proceedings, since obtaining a decision by the interested party in this way – which takes into account the applicant’s request – makes it most often unnecessary to continue the proceedings through an appeal or administrative court.